Effect of graywater irrigation on soil quality and fate and transport of surfactants in soil - Negahban Azar, Masoud, author; Sharvelle, Sybil, advisor; Carlson, Kenneth, committee member; Stromberger, Mary, committee member; Durnford, Deanna, committee member (Colorado State University. Libraries, 2012)
While interest in and adoption of graywater reuse for irrigation has rapidly grown in recent years, little is known about the long-term effects of graywater irrigation. Concerns exist in relation to the presence of pathogenic organisms, fate of personal care products, and accumulation of salts. The purpose of this research was to evaluate the long-term effects of graywater irrigation to soil quality. The specific objectives were to evaluate the effects of graywater application on physical and chemical quality of soil, including surfactants, salts and boron accumulation, organic matter leaching and soil hydrodynamic properties in real environment in the field, in controlled environment in the greenhouse and column studies. In addition, fate and transport of surfactants in soil were investigated including how surfactant characteristics impacts mobility in soil of varying types. Graywater irrigation was found to significantly increase sodium in soil at households with graywater systems in place for more than five years; however SAR was not high enough in any of the sampling locations to raise concern about soil quality or plant health. There is a potential for salts, N, and B to leach through soil when graywater is applied for irrigation. A portion of the applied N is assimilated by plants, but leaching of N was observed. Graywater irrigation was also found to significantly increase surfactants in soil. Surfactants mainly accumulated in surface soil (0-15 cm) compared to depth soil. While surfactants have high sorption capacity due to their hydrophobic characteristics, they can be transported through soil if a large amount of water is applied. Among the surfactants measured in this study, AS and AES had the highest mobility. Mobility of surfactants in soil decreased when their number of ethoxylated groups increased. Adding organic matter to the soil increased sorption capacity of soil, as a result, more surfactants retained in the soil columns. Antimicrobials, including triclosan and triclocarban were detected in graywater irrigated areas only in surface soil samples, but not freshwater irrigated areas.
Keywords: surfactants; graywater; soil quality; irrigation